Musicology, Performance, Slavery: Intellectual Despotism and the Politics of Musical Understanding - Parmer, Dillon (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2014)
This essay focuses on the uneasy relationship between scholarship and performance. I argue that this uneasiness stems from a still pervasive hierarchy, one that gives scholarship the power to regulate, even repress, what musicians themselves know and understand of music through the act of performing. This relation has far-reaching consequences that not only underscore basic epistemological formulations concerning the nature of both music and performance, but also govern what constitutes authoritative knowledge about the art. Indeed, in the modern research university, this relationship effectively accords epistemological legitimacy to every institutional identity that has something to say about music except that of the musician herself. If the musician and her activity figure in, they do so in subordinate positions, as objects to be studied, interviewed, prodded, or measured, or as vehicles for the application of disciplinary or research-based understanding. Such a situation enacts a power dynamic disturbingly similar to those operative in political structures founded on class difference, social inequality, and slavery. Indeed, I trace this dynamic back to Aristotle’s Politics, where his defence of slavery effectively separates the work of thought from that of the body so as to keep thought elevated and pure. The relevance of this separation to musical matters becomes explicit in Boethian music theory, where those who merely think about music become musical authorities, while those who make music (whether as composers or performers) remain largely ignorant of what they are doing. Excerpts from musicological literature past and present show that this division, what might be called “intellectual despotism,” continues to underwrite institutional music discourse in at least four salient ways: (1) by distorting music from a practice into an object to be observed; (2) by privileging listener-spectatorship and the experience of music had therein; (3) by promoting to sole epistemological authority those who speak to music through the mouthpieces of other disciplinary voices; and finally (4) by constructing musicians as benighted subjects who need to be “educated,” “informed,” or “civilized” by scholarship. The article concludes by outlining a program for undermining this politics, one that places musicians, as well as the knowledge embodied in music-making, at the foundation of musical understanding.